Functionalization of dipyrromethanes via hetero-Diels–Alder reaction with azo- and nitrosoalkenes - Pereira, Nelson A. M. (2014)
5,50-Diethyl- and 5-phenyldipyrromethanes participate in cycloadditions with azo- and nitrosoalkenes giving dipyrromethanes with side chains containing open chain oximes and hydrazones. By controlling reaction stoichiometry it is possible to get mono or 1,9-disubstituted derivatives. The reported methodology gave access to a range of dipyrromethanes with good structural features for various applications. It was demonstrated that reduction of dipyrromethanes containing a-oximino ester groups opens the way to new a-amino esters.